Identification of Xanthomicrol as a Major Metabolite of 5-Demethyltangeretin in Mouse Gastrointestinal Tract and Its Inhibitory Effects on Colon Cancer Cells - Wu, Xian; Li, Zhengze; Sun, Yue; Li, Fang; Gao, Zili; Zheng, Jinkai; Xiao, Hang (Frontiers in Nutrition, 2020)
5-Demethyltangeretin (5DT) is a unique polymethoxyflavone mainly found in the peel of citrus, and have shown potent suppressive effects on multiple human cancer cells. Biotransformation plays a critical role in the biological activities of dietary bioactive components because their metabolites may exert significant bioactivities. In the present study, the metabolic fate of 5DT in mouse gastrointestinal (GI) tract after long-term oral intake and the anti-cancer effects of its major metabolite were determined. It was found that 5DT underwent extensive biotransformation after oral ingestion in mice. A major demethylated metabolite was produced via phase I metabolism, while conjugates (glucuronide and sulfate) were generated via phase II metabolism. Specifically, 4'-position on the B ring of 5DT was the major site for demethylation reaction, which led to the production of xanthomicrol (XAN) as a major metabolite. More importantly, the level of XAN in the colon was significantly higher than that of 5DT in 5DT-fed mice. Thus, we further determined the suppressive effects of XAN on human colon cancer HCT116 cells. We found that XAN effectively inhibited the proliferation of HCT116 cells by arresting cell cycle and inducing cellular apoptosis, which was further evidenced by upregulated p53 and p21 and downregulated cyclin D and CDK4/6 level. In conclusion, this study identified XAN as a major metabolite of 5DT in mouse GI tract, and demonstrated its suppressive effects on HCT116 colon cancer cells.